Recent discoveries of alien Watersipora (Bryozoa) in Western Europe, with redescriptions of species - Ryland, John S.; de Blauwe, Hans; Lord, Richard; Mackie, Joshua A. (Zootaxa, 2009)
We report the introduction of the encrusting bryozoan Watersipora subtorquata to Atlantic coasts of Europe. This species is highly invasive, having become common on coastlines throughout cool-temperate areas of the world since the 1980s. Confusion exists over the identity of this and other Watersipora species, which lack characters that are conventionally used in bryozoan systematics. W. subtorquata has not been well distinguished from W. cucullata which, reports dating back to the mid 1800s suggest, is native to the Mediterranean Basin or represents an early shipping introduction. W. cucullata has been placed in synonymy with W. subovoidea, a taxon lacking a holotype. We designate a neotype for W. subovoidea, recognizing its conspecificity with W. cucullata, and demonstrate a simple morphometric means of separating this species from W. subtorquata using zooid feature ratios (operculum area versus total frontal shield). An orange watersiporid population that was first recognized in Guernsey, in the European-Atlantic, in 2007, is shown by morphometric and mitochondrial genetic analysis to match W. subtorquata. It contains the commonest, widely introduced COI haplotype that, along with other evidence, suggests recent transfer via shipping traffic to Europe. A second population (previously referred alternatively to W. aterrima or W. subovoidea) has been reported from Brittany and Bordeaux (Atlantic coastline, France). This population is also aligned with W. subtorquata based on morphometrics and COI haplotype. In contrast to the Guernsey introduction, the earlier French-Atlantic introduction appears related to oyster imports from Japan.